The relevance of academic advising with the use of video tutorials - Sánchez-Aldape, José Alfredo (Universidad Autónoma de Tamaulipas, 2018)
This study analyzes the development and implementation of an academic advising model using video tutorials in university students of the Business School in the Universidad Autónoma de Tamaulipas. The use of ICT as a support to enhance academic pursuits in higher education students is one of the actions that have contributed to the reduction of failure and dropout rates in universities. From this approach, the aim of this study is to strengthen the remedial academic advising, through the use of video tutorials, especially in those disciplines where there is a high rate of school failure.